Notes for the improvement of the conceptual contents of the Instituciones de Derecho Privado course (PUCP) - Campos García, Héctor (2021)
This document analyzes the conceptual contents of the Private Law Institutions course in the New Study Plan of the Faculty of Law of the Pontificia Universidad Católica del Perú. Two problems are addressed. Firstly, the possible overlaps with the conceptual contents of other courses of the New Plan such as Legal Science Introduction or Fundamental Rights and Constitutional Interpretation. Secondly, the set of topics that are not developed despite being part of the thematic units of the course. Finally, recommendations are made to deal with the aforementioned problems.